Dynamics of Mahar in Marriage: A Philosophical and Sociological Approach in Islamic Family Law - Abdul Ali Mutammima Amar Alhaq; Najib Mahfuzh; Ikmal Maulana (CV. Abhinaya Indo Group, 2025)
Dowry is a fundamental element in Islamic marriage that has legal, social and philosophical significance. In Islamic law, dowry is an obligation that must be given by the husband to the wife as a form of respect and proof of commitment in marriage. The dowry also serves as a financial protection for women, especially in societies where men are the main breadwinners. From a sociological perspective, dowry reflects social status, gender relations, and cultural norms that develop in society. However, in some cases, the size of the dowry can become an economic burden for the prospective husband and hinder the marriage. From a philosophical perspective, the dowry reflects respect for women's dignity and moral responsibility in marriage. The dowry is not a medium of exchange in the marriage contract, but a manifestation of justice, balance, and respect for rights and obligations in the household. The ideal dowry concept must consider the principles of justice and welfare for both parties, without being an instrument of exploitation or domination. This research uses a qualitative approach with a literature study method to understand the role and meaning of dowry in legal, social and philosophical contexts. The results show that dowry has complex social and moral dimensions, which need to be understood in the context of the culture and dynamics of modern society. Therefore, a more flexible understanding of dowry is needed so that it remains relevant to the times, without losing its essential values in Islam. Legal regulations and social norms related to dowry should be based on the principle of balance, so that marriage can take place with values that support justice, harmony and prosperity for both parties.